The Colloidal Quantum Dots Suitability for Long Term Cell Imaging - Farias, Patricia M. A.; Galembeck, André; Milani, Raquel; Mendonca, Wilson S.; Stingl, Andreas (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Fluorescent semiconductor nanoparticles in tree-dimensional quantum confinement, quantum dots (QDs), synthesized in aqueous medium, and functionalized with polyethylene glycol, were used as nonspecific nanosized probes for the long-term imaging of glial cells. In vitro living healthy as well as cancer glial cells were labelled by direct insertion of a small volume of QDs contained in aqueous suspension into the culture wells. A long-term monitoring (over 7 days) of the cells was performed and no evidence of cell fixation and/or damage was observed. Two control groups, healthy and non-healthy glial cells, were used to compare cell viability. During the observation period, labelled cells kept the same behavior compared to non-labelled control samples. To our knowledge, this is the first report of the viability of quantum dots for long-term imaging of living cells. This opens a large range of possibilities related to a better understand of cellular mechanisms, which till now was not achieved by any other fluorescent probe. The study also permitted the observation of two distinct interaction kinetics between cells and QDs. Healthy glial cells were mainly labelled at their surface, while non-healthy glial cells have shown a high rate in the uptake of QDs.